The immunology of infection - Gilchrist, JJ; MacLennan, CA (Elsevier, 2021)
The human immune system is composed of a collection of specialized cells and secreted proteins that allows the identification and removal of an invading pathogen, and in doing so limits host injury or death. This system is composed of innate and adaptive branches. It is important to recognize that although the innate and adaptive branches of the immune system differ fundamentally in their mechanisms of pathogen recognition, neither branch functions in isolation. In this article, we address how the innate and adaptive immune systems sense the presence of a pathogen, how the immune system then coordinates anti-pathogen effector functions to remove the pathogen, and how immunological memory functions to better protect its host against subsequent exposure to the same pathogen. Finally we consider how vaccines harness the immune system to induce protective immunity against infection and how controlled human infection models can inform our understanding of the immunology of infection.